An investigation of the views and perceptions of external users of corporate annual reports in emerging economies: the case of Egypt. (4th August 2010) - Dahawy, Khaled; Samaha, Khaled
The purpose of this paper is to examine how users of company annual reports in the emerging market of Egypt view those reports, and to compare the results with the findings of Mirshekary and Saudagaran (2005) in Iran. Each study is based on a survey of different but comparable user groups in the respective country. The data reported in this study were collected through a questionnaire survey, covering six user groups. The 72 responses received were analysed using the Kruskal-Wallis one-way ANOVA test. The results reveal that most use annual reports for obtaining information for financial decisions. The paper also reveals that, in comparison with developed markets, Egyptian users depend more on annual report information than on advice from stockbrokers and friends or on tips and rumours. The respondents, in general, ranked the auditors' report, notes to the financial statements and the balance sheet as the three most important parts of the annual report. However, the respondents differed in their rating of the importance of different sections of the annual report. Despite the lack of access to these reports by the general public and lack of trust in information, the majority of users view annual reports as the most important source of company information. The results further indicate that the ranking reported by users in Egypt is notably different from that reported in Iran. This supports the research stream that aims to study accounting at single-country levels. It also sends the message that developing countries are different and face different problems from developed ones. Therefore, there might be a need to reconsider the one-size-fits-all standards that are recommended by the International Accounting Standards Board (IASB). There is an important level of adjustment which a country that imports accounting standards must make to ensure that they do not conflict with the local socioeconomic culture.